2021
DOI: 10.1186/s12961-021-00761-7
|View full text |Cite
|
Sign up to set email alerts
|

Community health workers at the dawn of a new era

Abstract: Background There is now rapidly growing global awareness of the potential of large-scale community health worker (CHW) programmes not only for improving population health but, even more importantly, for accelerating the achievement of universal health coverage and eliminating readily preventable child and maternal deaths. However, these programmes face many challenges that must be overcome in order for them to reach their full potential. Findings T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 31 publications
2
34
0
1
Order By: Relevance
“…Securing sustainable financing for community health worker programmes can be a challenge, particularly as in many countries these rely on external funding. 37 Debates about paying community health workers typically focus on the trade-offs between reliance on volunteerism underpinned by intrinsic motivation of volunteers and the need to recognise and remunerate work fairly (and in doing so, addressing gender disparities, as most of the community health worker workforce is female). 38 , 39 Section 5 includes a brief summary of the evidence on paying community health workers.…”
Section: Section 1: Financing Primary Health Care In the 21st Century...mentioning
confidence: 99%
“…Securing sustainable financing for community health worker programmes can be a challenge, particularly as in many countries these rely on external funding. 37 Debates about paying community health workers typically focus on the trade-offs between reliance on volunteerism underpinned by intrinsic motivation of volunteers and the need to recognise and remunerate work fairly (and in doing so, addressing gender disparities, as most of the community health worker workforce is female). 38 , 39 Section 5 includes a brief summary of the evidence on paying community health workers.…”
Section: Section 1: Financing Primary Health Care In the 21st Century...mentioning
confidence: 99%
“…This result is consistent with our hypotheses that CHWs can increase coverage of acute malnutrition treatment. Zulu and Perry 2021, in a recent series found that the large-scale involvement of CHWs in the health care system has a huge potential for accelerating universal health coverage and improving population health [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…A cursory reader well-versed in CHW programs (for example, the 20-year-old seminal publication of Bhattacharyya et al on CHW incentives and disincentives 5 ) might be forgiven for pondering, “We already know that both financial and nonfinancial incentives matter if we want motivated and performing CHWs. What is new in this?” The question is timely as a new Health Research Policy and Systems 6 supplement issue (including a summation of lessons on incentives and remuneration of CHWs 7 ) now updates the work of Bhattacharyya et al, 5 the CHW Reference Guide, 8 and more recently, the 29 country case studies by Perry on national CHW programs. 9 Indeed, some findings recur across contextual studies and accrue a recognizable body of evidence, even if they do not have the sharp edges of controlled experiments.…”
Section: Introductionmentioning
confidence: 99%